2019
DOI: 10.1007/s00425-019-03245-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cell-wall polysaccharides and proteins during growth of the hemp hypocotyl

Abstract: Main conclusion The immuno-ultrastructural investigation localized cell-wall polysaccharides of bast fibers during hemp hypocotyl growth. Moreover, for the first time, the localization of a peroxidase and laccase is provided in textile hemp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
0
12
1
Order By: Relevance
“…We analyzed olive leaves of both varieties taken at 3 selected time points (T0, T4, and T8). The protocol is detailed in Behr et al [ 64 ]. For transmission electron microscopy (TEM), samples were fixed in 3% glutaraldehyde in cacodylate buffer (0.066 M, pH 7.2), for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed olive leaves of both varieties taken at 3 selected time points (T0, T4, and T8). The protocol is detailed in Behr et al [ 64 ]. For transmission electron microscopy (TEM), samples were fixed in 3% glutaraldehyde in cacodylate buffer (0.066 M, pH 7.2), for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The RG-I with long galactan side chains is crucial in forming specific tertiary cell wall architecture (Gorshkova et al, 2010(Gorshkova et al, , 2018Guedes et al, 2017). Either a galactan or RG-I backbone can be labeled in tertiary cell walls using LM5 or RU2 antibodies, respectively, depending on the plant species (Gorshkova et al, 2004;Chernova et al, 2018;Behr et al, 2019). The binding of LM5 to the thickened cell walls of xylem fibers was detected on the pulling side of the inclined flax (Figure 2).…”
Section: Xylem Fibers Deposit Tertiary Cell Wall In the Gravitropic Rmentioning
confidence: 99%
“…These layers have an exceedingly high content of cellulose (Norberg and Meier, 1966) and close to axial orientation of cellulose microfibrils (Clair et al, 2011). Xylan is absent (Gorshkova et al, 2015;Chernova et al, 2018;Behr et al, 2019), as is lignin (Love et al, 1994;Kaku et al, 2009;Gorshkova et al, 2012). The latter, however, can sometimes be deposited at a late stage of fiber maturation (Roussel and Clair, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose crystallinity varies with the plants' tissue type and age. An emblematic example is represented by fiber crops: Recently we have shown that, during development, the gelatinous layer in the bast fibers of the hemp hypocotyl undergoes compaction with the transition from a fibrillary texture to a homogeneous layer [13]. As the hypocotyl ages, cellulose crystallinity is a mechanical requirement for the bast fibers which support the stem and, more specifically, the vascular tissue (phloem) of the growing plant.…”
Section: Properties Of Plant Fibers and Characterization Of Cellulosementioning
confidence: 99%
“…Plasma treatment of ramie fibers was used to increase the microroughness of the surface, hence increasing the surface area available for bonding [12]: After only one minute of treatment, nanostructures caused by the exposed cellulose microfibrils were visible and an increased wettability (using a mixture of phenolic resin and its catalyst as test liquid) was recorded. Among the chemical treatments, the use of alkali (i.e., mercerization) is one of the most common: NaOH is used to remove pectins and non-cellulosic polysaccharides, thereby disassembling the bundles and making the fiber surface rougher and cleaner [13]. The alkali treatment affects the tensile properties of the fibers by affecting the cellulose crystalline lattice (cellulose-I polymorph): Swelling is induced, as Na+ penetrates the pores of the lattice, thereby favoring the entry of water molecules which will increase the distance between the cellulose fibrils [21].…”
Section: Figure 2 Cartoon Showing the Crystalline And Amorphous Regimentioning
confidence: 99%